HUBUNGAN PENGGUNAAN APLIKASI PESAN-ANTAR MAKANAN, ASUPAN LEMAK, DAN AKTIVITAS FISIK DENGAN STATUS GIZI LEBIH PADA SISWA SMAN 63 JAKARTA - Aurelia Gracia Chiquita Sony (2023)
Background: Based on Riskesdas data in 2018, there are 13,5% of adolescents aged 16-18 years are overweight and obese. Dietary changes along with the times are a factor causing changes in nutritional status. Objective: To find the relationship between the usage of food delivery applications, fat intake, and physical activity with overweight status of students at SMAN 63 Jakarta. Methods: The research design used a cross-sectional study involving 77 students in grades X and XI. Results: Chi-square analysis results showed that the frequency of delivery application usage had a relationship with overweight status in adolescents (p = 0.000). There is no relationship between the type of food ordered and overweight status of adolescents (p = 0.467). There is no relationship between the amount of food ordered and overweight status of adolescents (p = 0.655). There is a relationship between fat intake and overweight status in adolescents (p = 0.000). There is a relationship between physical activity and overweight status in adolescents (p = 0.006). Conclusion: There is a relationship between the frequency of delivery application usage, fat intake, and physical activity with overweight status, there is no relationship between the type and amount of food ordered and overweight status.